ANALISIS CO-WORD BERBASIS APLIKASI VOSViewer PADA ARTIKEL DENGAN TOPIK COVID-19 DI INDONESIA CO-WORD ANALYSIS BASED ON THE VOSViewer APPLICATION IN THE ARTICLE WITH THE TOPICS COVID-19 IN INDONESIA - Winoto, Yunus (Publication Library and Information Science, 2023)
The occurrence of the Covid-19 outbreak has not only changed various ways of life in society, especially in Indonesia, but the Covid-19 pandemic has also encouraged various academics and researchers to carry out various studies on Covid-19 in Indonesia from various perspectives. Furthermore, from the results of these studies and research, some of them were published in journals, both international and national journals. This study aims to conduct a Co-Word-based mapping analysis on articles on the topic of Covid-19 in Indonesia, which are in the dimensions database network published in the period 2019-2020 which includes the most followed authors, the documents that have the most influence. other documents and the most influential authors for other authors. The method used in this research uses citation analysis and descriptive evaluative methods. The population in this study is data in the form of articles with the topic â€œCovid-19 in Indonesiaâ€ which is taken through the dimensions database published in 2020. By using search in free text in title and abstract there are 289 article titles that have been published in Dimensions in 2020. Based on the results of the research, it is known that there are two authors or authors who write topics about Covid-19 in Indonesia that are most followed by other authors, namely Sofia Al Farizi and Bagus Nuari Harmawan; The most cited document is a document entitled, "Patterns of Covid-19 Mortality and Vitamin D: An Indonesian Study from the SSRN Electronic Journal" with the author's citation Rahasusun in 2020 which is cited by other documents as many as 30 documents. Meanwhile, the second document is entitled The Impact of Covid-19 of to Indonesian Education and its Relation to the philosophy of "Merdeka Learning", with the author's citation Adiba. This document has been cited by other documents 5 times. The most influential author is Arry Yanuar, where the author Arry Yanuar is located in two clusters and is connected with 160 link strenght.